Diagnostic Accuracy of Plasma Ghrelin Concentrations in Pediatric Sepsis-Associated Acute Respiratory Distress Syndrome: A Single-Center Cohort Study - Yuan, Xiu; Li, Shaojun; Zhou, Liang; Tang, Tian; Cheng, Yuwei; Ao, Xiaoxiao; Tan, Liping (Frontiers in Pediatrics, 2021)
Abstract Background: Ghrelin is the endogenous ligand of growth hormone secretagogue receptor 1a (GHSR1a), which can regulate immunity and inflammation. To assess the diagnostic value of plasma ghrelin levels in sepsis-associated pediatric acute respiratory distress syndrome (PARDS). Methods: We recruited patients from the PICU of a third-class teaching hospital who met the diagnostic criteria for sepsis from January 2019 to January 2020. Clinical data, laboratory indicators, plasma ghrelin concentrations, and inflammatory factors of cohort were evaluated in detail, and patients were followed up for 28 days. The area under the receiver-operating characteristic curves (AUROC) was calculated using logistic regression to calculate and positivity cut-offs was tested. Ghrelin's ability to diagnose and differentiate sepsis-associated PARDS were determined. The log-rank test was used to compare the survival curves of different ghrelin level groups. Main results: Sixty-six PICU patients (30 with ARDS, 36 without ARDS) who met the diagnostic criteria of sepsis were recruited. The ghrelin level was significantly higher in the sepsis patients of the ARDS group than in those of the non-ARDS group. The AUROC of ghrelin was 0.708 (95% confidence interval: 0.584–0.833) and the positivity cutoff value was 445 pg/mL. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (+LR), and negative likelihood ratio (–LR) of plasma ghrelin for diagnosis of sepsis with PARDS were 86.7%, 50.0%, 59.1%, 81.8%,1.734, and 0.266, respectively. The survival rate of sepsis patients was significantly improved when the ghrelin level was >445 pg/mL. Conclusions: Ghrelin plasma was higher in sepsis-associated PARDS, and accompanied by the increase of inflammatory factors. The increased plasma ghrelin may be due to the anti-inflammatory response, which may be a protective factor in children with sepsis. Yet, there is no evidence to prove that elevated ghrelin appears to be a promising diagnostic indicator of sepsis-associated PARDS. In addition, the ghrelin levels may be a positive predictor of sepsis.